PELATIHAN ROBOT LINE FOLLOWER ANALOG BAGI SISWA SMK TKM TEKNIK PURWOREJO - Muhammad Andang Novianta; Beny Firman (LPPM IST AKPRIND Yogyakarta, 2021)
The curriculum in many schools is adapted to technological developments. One of theincreasingly sophisticated technological developments in the era of the industrial revolution4.0 is robotics. Along with the shift in the direction of the world of education, which issynchronized with technological advances, the SMK Taman Karya Madya (TKM) PurworejoEngineering intends to provide the ability, skills, knowledge, and competencies or students'love for robotics technology. This community service aims to provide an introduction ortraining that is packaged in the form of a day workshop to be able to attract the interestsand talents of SMK TKM Engineering students Purworejo to know the basics of robotics,hardware components, software, and to design robot hardware and software especially LineFollower (Line Follower Robot). The results of this activity students are able to understandthe basic components and concepts of line follower robot programming and can also makeor assemble a line follower robot module well, as evidenced by the operation of the robotthat is assembled by students. The formation of a new robotics team at SMK Taman KaryaMadya (TKM) Purworejo Engineering as preparation in facing similar national robotcompetitions.